(untitled) (Journal of the College of Basic Education, 2022)
The current research focuses on the design of a three-electrostatic electrostatic lens with the least aberration using the analysis method, which is one of the common methods in designing lenses and by choosing a suitable shape for the poles of this lens, then studying the voltage distribution on these poles from the solution of the Laplace equation and from the solution of the axial beam equation to find the path of the particles, which achieves imposed voltage equalization.In this paper, an immersed electrostatic lens was designed, where the shape of the poles of the lens was obtained in two dimensions using the solutions of the Laplace equation. And he has